Diversity of Feed Storage Pest Beetle in Banten Province - Nasrul Friamsa; Witjaksono Witjaksono; Arman Wijonarko (Universitas Gadjah Mada, 2018)
Banten province is a growing industrial area, where many industrial items were prepared including animal feed whose raw materials are mostly imported from abroad. Therefore, monitoring feed storage is very important to ensure the existence of pest insects in storage warehouse and to prevent the entry of plant quarantine pest organism (OPTK) which may be carried by imported feed raw materials. The identification, diversity and evenness of pest beetle species in five feed storages in Banten province region have been done. Feed sampling was done using hand sampling method. Samples taken from the diagonal corner and center of storage, respectively as much as 250 grams four times within one-week interval. The results were that 13 species of pest beetles from seven families were intercepted. Cryptolestes ferrugineus, Rhizoperta dominica, and Tribolium castaneum pest beetles were the dominant insects attacking five storages. Specifically, the dominant pest beetles in each commodity were: T. castaneum on soybean meal (SBM); C. ferrugineus and T. castaneum on corn; T. castaneum and R. dominica on corn gluten meal (CGM); T. castaneum and Sitophilus zeamais on wheat; T. castaneum on soybeans; and Oryzaephilus surinamensis in sorghum. Environmental factors, the type and duration of stored commodities were found to be the factors supporting the existence of pest beetle species. The highest diversity of pest beetle varieties was found in warehouse A with a value of 1.552 which was considered as moderate diversity. The evenness index of pest beetle species showed that warehouses A and E were in unstable conditions. Meanwhile, the warehouses B, C, and D were in depressed conditions dominated by certain species of pest beetle. IntisariProvinsi Banten merupakan daerah industri yang terus berkembang, termasuk industri pakan ternak yang bahan bakunya sebagian besar diimpor dari luar negeri. Oleh sebab itu, pengawasan terhadap gudang penyimpanan pakan sangat penting dilakukan untuk mengawasi keberadaan serangga hama pada gudang penyimpanan dan mencegah masuknya Organisme Pengganggu Tumbuhan Karantina (OPTK) yang mungkin terbawa bahan baku pakan yang diimpor. Identifikasi, keanekaragaman serta kemerataan jenis kumbang hama pada lima gudang penyimpanan pakan di wilayah Banten telah dilakukan. Pengambilan sampel bahan pakan menggunakan metode hand sampling. Sampel diambil pada bagian sudut dan bagian tengah secara diagonal masing-masing sebanyak 250 gram sebanyak 4 kali dengan interval waktu 1 minggu sekali. Hasil penelitian diperoleh 13 jenis kumbang hama dari 7 famili. Kumbang hama jenis Cryptolestes ferrugineus, Rhyzoperta dominica, dan Tribolium castaneum merupakan serangga yang dominan menyerang kelima gudang penyimpanan. Jenis kumbang hama yang dominan pada masing-masing komoditas adalah T. castaneum pada soybean meal (SBM); C. ferrugineus dan T. castaneum pada komoditas jagung; T. castaneum dan R. dominica pada corn gluten meal (CGM); T. castaneum dan Sitophilus zeamais pada gandum; T. castaneum pada kedelai; dan Oryzaephilus surinamensis pada sorgum. Faktor lingkungan, jenis dan lama komoditas yang disimpan merupakan faktor pendukung keberadaan suatu jenis kumbang hama. Indeks keanekaragaman jenis kumbang hama tertinggi ditemukan pada gudang A dengan nilai 1,552 menggambarkan keanekaragaman tergolong sedang. Nilai indeks kemerataan jenis kumbang hama menunjukkan bahwa gudang A dan gudang E termasuk dalam kondisi labil; sedangkan gudang B, C, dan D termasuk dalam kondisi tertekan dengan didominasi oleh jenis kumbang hama tertentu.